The Misuse of China's R&D Subsidies: Estimating Treatment Effects With One-Sided Noncompliance - Philipp Boeing; Bettina Peters (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
We investigate the misuse of R&D subsidies and evaluate its consequences for policy effectiveness. Developing a theoretical framework and using Chinese firm-level data for 2001-2011, we identify that 42% of grantees misappropriated R&D subsidies for non-R&D purposes, accounting for 53% of total R&D subsidies. Misuse leads to a substantial loss in the causal impact of R&D subsidies, as measured by the difference between the intention-to-treat and complier average causal effect. R&D expenditures could have been stimulated beyond the subsidy amount (additionality), but misuse (noncompliance) resulted in medium-level partial crowding out, reducing the effectiveness of China's R&D policy by more than half.
Keywords: O31; O38; C21; H21; 330; R&D subsidies; policy evaluation; misuse; China